2016
DOI: 10.1161/circinterventions.116.003779
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Backward-Traveling Decompression (Suction) Wave Correlates With Simultaneously Acquired Indices of Diastolic Function and Is Reduced in Left Ventricular Stunning

Abstract: 4As coronary flow is predominantly diastolic, the predominant driver of coronary flow, particularly in the left coronary artery, 5 is thought to be the BEW (or suction wave), generated by myocardial microcirculatory decompression in early diastole. 4 It has been suggested that the measurement of the BEW might have future utility in testing myocardial viability at the time of percutaneous coronary intervention (PCI) 6 or even predicting the timing of intervention in aortic valve disease. 7 The BEW has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
2
13
1
1
Order By: Relevance
“…In the experimental data, a strong correlation was found between the size of the incident wave (FDW A→C ) and BDW dia (R 2 > 0.6), but there was no correlation with LV τ and only a weak-to-moderate correlation with LV dP/dt min (R 2 = 0.3) that lost significance in a multivariate model. Previous studies have reported R 2 values of 0.21−0.35 between LV dP/dt min and the coronary BDW dia , in agreement with our findings (Kyriacou et al 2012;Ladwiniec et al 2016), although Ladwiniec and colleagues also reported a correlation (R 2 = 0.35) between LV τ and BDW dia (Ladwiniec et al 2016).…”
Section: Early-diastolic Backward Decompression Wave (Bdw Dia )supporting
confidence: 92%
See 4 more Smart Citations
“…In the experimental data, a strong correlation was found between the size of the incident wave (FDW A→C ) and BDW dia (R 2 > 0.6), but there was no correlation with LV τ and only a weak-to-moderate correlation with LV dP/dt min (R 2 = 0.3) that lost significance in a multivariate model. Previous studies have reported R 2 values of 0.21−0.35 between LV dP/dt min and the coronary BDW dia , in agreement with our findings (Kyriacou et al 2012;Ladwiniec et al 2016), although Ladwiniec and colleagues also reported a correlation (R 2 = 0.35) between LV τ and BDW dia (Ladwiniec et al 2016).…”
Section: Early-diastolic Backward Decompression Wave (Bdw Dia )supporting
confidence: 92%
“…; Ladwiniec et al . ; Raphael et al . ) and has been interpreted to arise from transmission of the aortic FCW dia into the coronary arteries (Davies et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations